(S)-(-)-limonene fumigation protects waxflowers (Chamelaucium spp.) from detrimental effects of ethylene on abscission of flowers/buds - Payne, Alan; Singh, Zora; Abdalghani, S.; Seaton, K. (Southern Cross Publishing, 2018)
Waxflowers are economically important native cut flowers in Australian floriculture industry. Postharvest flowers/buds abscission on stems of waxflowers causes serious economic losses to the Australian waxflower industry. The effects of (S)-(-)-limonene in reducing the damaging effects of ethylene on abscission of flowers/buds in six varieties of Geraldton waxflowers ‘WX73’, ‘WXFU’ ,‘WX17’, ‘WX58’, ‘WX56’ and ‘Purple Pride’ were investigated in 2014 and 2015. All the experiments were conducted having four treatments. The flowers stems were fumigated with ethylene (10 µLL-1) for 24 h and (S)-(-)-limonene (1 µM) alone for 18 h and (S)-(-)-limonene fumigation followed by exposure to ethylene. Untreated sprigs served as control. All the six experiments were laid out by following two-factor factorial completely randomised design including the (4 treatments and 4 times) with three replications and three stems were treated as an experimental unit. Cumulative abscission of flowers/buds was calculated for four consecutive days following 24 h of ethylene exposure. Fumigation with (S)-(-)-limonene (1 µM) for 18 h followed by exposure to 10 µLL-1 ethylene significantly reduced flowers/buds abscission as compared to ethylene treatment alone in all varieties except ‘WX17’. Mean flowers/buds abscission was significantly reduced when flower stems were fumigated with (S)-(-)-limonene followed by exposure to 10 µLL-1 ethylene (26.7%, 30.9%, 62.4%, 13.6 and 6.4%) as compared to those exposed to ethylene treatment alone (89.9%, 82.0%, 77.4%, 85.9% and 68.8%) in ‘WX73’, ‘WXFU’, ‘Purple Pride’, ‘WX56’ and ‘WX58’ respectively. ‘WX17’ waxflower fumigated with (S)-(-)-limonene followed by exposure to 10 µLL-1 ethylene did not show a significant reduction in flowers/buds abscission as compared to ethylene alone probably this genotype is more sensitive to ethylene because of their inherited trait. The results suggest that (S)-(-)-limonene act as an antagonist to ethylene action and consequently reduced flowers/buds abscission in waxflowers.